PENGEMBANGAN E-MODUL MATA KULIAH MOTOR BAKAR DENGAN METODE 4-D DI PRODI PENDIDKAN TEKNIK MESIN UNIVERSITAS SEBELAS MARET - Muhammad Reidho Ilham Azhari Azhari; Ranto Ranto; Husin Bugis (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
The development of science and technology is currently very developed with a lot of development in various fields, one of which is in the field of education, with the development of science in the world of education making it easier for all sectors in education, especially in the educational process, making it easier for students or students to learn and making it easier for educators to harden learning to be more enjoyable. This research has the objective, namely: to develop teaching materials in the combustion motor course that are adjusted to meet the needs and characteristics of students. The research method used in this research is teaching material research using the 4d development model adopted from Thiagarajan, et al (1974) which consists of 4 stages, namely define, design, develope and disseminate or can also be interpreted with 4p as follows: pendefinisian, perancangan, pengembangan, dan penyebaran. The data collection technique in this study uses a validation method consisting of questionnaire validation and expert validation (material expert validation, media expert validation, and linguist validation), This research also uses the focus group discussion method with various experts in their fields.Based on the results of the research obtained in the research on the development of the e-module of the combustion motor course, it shows that the results of expert validation carried out get decent Sanagat results with validation results from several aspects, namely: material expert validation shows the average result of the assessment with a percentage result of 90% (very feasible), expert validation shows the average result of the assessment with a percentage result of 97% (very feasible), linguist validation shows the average result of the assessment with a percentage result of 90% (very feasible) From the various validations carried out also received criticism / suggestions / input from various experts who assessed the improvement of the e-module. The results obtained from the focus group discussion conducted with experts in the field of automation produced several points of view on the electronic module of this combustion motor in the form of advantages and disadvantages so that improvements must still be made to the module, so that this electronic module of the combustion motor is carried out in a limited distribution in the Mechanical Engineering Education Study Program, Sebelas Maret University, Surakarta.